Influence of mechanical and thermal energy on rifampicin - Sundani N. Soewandhi; Kosasih .; Rachmat Mauludin; Irvan Khaeruddin (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2007)
The same raw material has opportunity to show different physical properties if it is produced by different industries. For such reason, rifampicin was chosen as a raw materials model, thats obtaining from five resource countries and were obtained from five different suppliers, each coded A, B, C, D and E. Each raw material was handled under tribomechanic and thermal treatment. Mechanical treatment was carried out by using grinding mill at 100 rpm for 30 minutes. Thermal treatment was carried out by oven at 105oC for 2 hours. Transformation occured, was identified by differential scanning calorymetry (DSC), X-ray powder diffraction and dissolution rate. The intrinsic dissolution rate was determined in 900 mL HCl 0,1N oxygen free, using basket and calculated through simultaneously determination method using uv spectrophotometry at λabs.maks. 475 nm. Thermograms of five milled raw material showed endothermic curve at 58oC without obviously melting curve.Thermogram of heated raw material did not show endothermic curve except its melting at 188oC-192oC. Crystallinity indices of the raw materials decreased from C, E, B, A to D. The milled raw materials were mixture of rifampicin II (2%) and amorphous (98%). A and D were mixture of rifampicin form II and fines (amorph). The other samples were only rifampicin form II. All of the raw materials showed different dissolution rates. Rifampicin B,C and D had sameness dissolution rate, whether milled or heated.Key words: Rifampicin II, rifampicin amorphous, DSC, powder X-ray diffraction, dissolution rate